Pengeloaan Sampah Rumah Tangga Menjadi Pupuk Cair dengan Menggunakan Komposter di Desa Tanjung Bulan, Kabupaten Kaur - Danang Adi Putra; Azizah Utami Putri; Deazella Aqila Isdianto; Mukhlish Raya; Ahmad Choirul (PT. Penerbit Riset Sadwa, 2026)
Processing household organic waste into liquid organic fertilizer using a composter is an effective approach to reducing organic waste while producing beneficial fertilizer for plants. This program aimed to improve the knowledge and skills of the residents of Tanjung Bulan Village through socialization, training, and hands-on practice in producing liquid organic fertilizer using a simple composter. The results showed that participants understood the process of waste sorting, EM4 bioactivator application, and fermentation to produce liquid organic fertilizer. The program also increased community awareness of household organic waste management and encouraged the utilization of liquid organic fertilizer for home gardening. Therefore, the use of composters can serve as a simple, environmentally friendly, and sustainable solution for household organic waste management